Znaczenie symboliki imienia „Мakar” w kontekście twórczości F.M. Dostojewskiego i problemów eschatologii jako skryty koncept życia i kreatywności kulturalnej człowieka - Krężołek, Olga (Studia Rossica Posnaniensia, 2011)
The paper deals with the meanings of the name Makar according to Florinsky's metaphysical conception which, with reference to the symbolic representation of simplicity in the oeuvre of Dostoyevsky and its problems of eschatology, make it possible to reveal the universal and cosmological message hidden in the symbolic content of the name. The name Makar as a symbol of the organic unity and the integrity of man's personality is rendered as a biblical universal model of the whole creation of which man is its expression. Man is meant as “God’s temple” which is “holy” i.e. ideal, as ideal is innocent man. Therefore, the name Makar in the oeuvre of Dostoyevsky is meant as the only valid conception of man's life and creativity which corresponds to God's Universe and protects man from further decline and degradation of life and culture because of its extreme measure.